Radiodense gastric contents in postmortem computed tomography. (March 2021) - Heimer, Jakob; Ebert, Lars; Thali, Michael; Ampanozi, Garyfalia
Highlights: A basic differentiation of intragastric food by radiodensity is possible. Spherical foods such as lentils may mimic the presence of intragastric pills. The radiodensity of intragastric food appears to be independent from the post mortem interval. Abstract: Background: Postmortem radiology often encounters foreign bodies in the stomach: food. Rarely, this intragastric content exhibits a high radiodensity, which can be confused with intragastric pills. We hypothesized that the radiodensity of this gastric content provided information about the interval between last meal and death. Methodology: The institutional database was searched for cases with high radiodense gastric contents seen on imaging. The postmortem interval was computed, and the interval between last meal and death was estimated. In addition, a simulation of postmortem gastric digestion was conducted. Samples of pasta, rice, lentils, chicken meat and broccoli were added to a gastric juice simulate. Computed tomography scans of the samples were repeatedly conducted for 4 h. Results: In total, 11 cases were included in the study. The gastric content was carbohydrates (rice, pasta, lentils) in six cases and meat in five cases. In both the cases and the experiment, maximum radiodensity of carbohydrates (>150 HU) was higher than of meat (100–150 HU) and vegetables (~50 HU, only experimental). Intragastric radiodensity did not correlate with the postmortem interval, and was stable in the experimental simulation apart from a decrease during the first 90 min for pasta and rice, which coincided with an increase of the radiodensity of the surrounding fluid. Conclusion: A differentiation of gastric content based on radiodensity and morphology is possible. All cases with high radiodensity had a short interval from last meal to death whenever computable. The radiodensity of intragastric food postmortem appears to be independent from the postmortem interval.